Revolutionizing Arabic Language Reading Skills Among Junior Islamic School Students via Innovative Digital Comic Learning Media - Diana Novita; Almaida Fitra Hamdala (WISE Pendidikan Indonesia, 2023)
This study explores the effectiveness of digital comic media in improving Qira'ah proficiency among seventh-grade students at MTs AL-Hikmah Bandar Lampung. It addresses three main research questions: (1) How does the development of digital comic media contribute to enhancing Qira'ah proficiency? (2) What is the feasibility of this digital comic media in promoting Qira'ah proficiency? (3) How do students respond to the implementation of this digital media? The research adopts a Research and Development (R&D) approach, guided by the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation phases. Findings reveal that the Arabic digital comic media was highly feasible, with media experts assigning an assessment score of 94.1% and material experts rating it at 91%. Additionally, student feedback reflected a strong positive response, with an average approval rate of 91%. Teacher evaluations yielded a score of 95.5%, further corroborating the tool's utility in the educational process. In conclusion, this study affirms the potential of digital comic media as an innovative and effective tool for enhancing Qira'ah skills in a junior high school context, contributing to the broader landscape of Arabic language learning methodologies.